Characterization of the regulatory function of the 46-kDa isoform of Rubisco activase from Arabidopsis - Zhang, Ning; Portis Jr., Archie R.; Schürmann, Peter (My University, 2004)
Arabidopsis Rubisco activase was recently shown to be regulated by redox changes in the larger (46-kDa) isoform specifically mediated by thioredoxin-f [Zhang and Portis (1999) Proc Natl Acad Sci USA 96: 9438–9443]. Reduction greatly increases the activity of the 46-kDa isoform and the native protein at physiological ATP/ADP ratios. In this study we conducted additional experiments to characterize the regulation of Rubisco activase by thioredoxin-f. The Km for both ATP hydrolysis and Rubisco activation by the 46-kDa isoform was lowered by 4 to 5-fold after reduction, but the maximum activity was increased by only 10%. Only 0.35 μM thioredoxin-f was required for a half-maximal activity change after a 10 min preincubation and activation with 1 μM was complete after 10 min. Equal amounts of 46-kDa and 43-kDa isoforms were required for a complete inhibition of the Rubisco activation activity after a reduction-oxidation cycle and assay at an ATP/ADP ratio of 3:1, whereas activity was only inhibited by 50% at a 2:1 ratio (43-/46-kDa) of the isoforms. This requirement is consistent with the fact that Arabidopsis normally contains about a 1:1 ratio of the two isoforms at both the mRNA and protein levels. Redox titrations indicated a midpoint potential of −344 mV for the 46-kDa isoform as compared to −342 mV for spinach fructose 1,6-bisphosphatase at pH 7.9, consistent with previous reports indicating that these proteins are co-regulated by light intensity in a similar manner.
Keywords: carbon metabolism; redox regulation; thioredoxin